Evaluation of Potential Antioxidant Activity of Leaves of Bauhinia Acuminate: Evaluation of Potential Antioxidant Activity of Leaves - Md. Reyad-ul-Ferdous; Farzana Liza; Tamara Towshin Alam; Fariha Tasnim; Mohsina Mukti; Md. Eshak Khan; Tazmel Haque (Iranian Journal of Pharmaceutical Sciences, 2014)
The methanol extracts of leaves of Bauhinia acuminata (MESF) and their different fractions obtained from modified Kupchan partitioning method i.e. methanol, pet ether, carbon tetrachloride, chloroform, and aqueous soluble fractions were subjected to biological screening such as total phenolic content and antioxidant activity screening.The amount of total phenolic content differed in different extractives and ranged from 15.90 mg of GAE/gm of extractives to 124.80 mg of GAE /gm of extractives of B. acuminate. Among all extractives of B. acuminate the highest phenolic content was found in AQSF (124.80 mg of GAE /gm of extractives) followed by CSF (103.78 mg of GAE /gm of extractives).Significant amount of phenolic compounds also present in CTCSF (75.59 mg of GAE /gm of extractives), MESF (66.20 mg of GAE /gm of extractives) and PETSF (15.90 mg of GAE /gm of extractives) were also found. The antioxidant activity of IC50 values in DPPH method differed in different extractives and ranged from 22.01 to 77.79. Among all extractives of B. acuminata the highest free radical scavenging activity was given by CTCSF (absorbance 22.01) followed by AQSF (absorbance 29.83).Significant free radical scavenging activity was also exhibited by CSF (absorbance 45.09), MESF (absorbance 43.78), PESF (absorbance 77.79).